Effect of polycarboxylate superplasticizer dosage on the mechanical performance of roller compacted Rubbercrete for pavement applications - Adamu, M. (Medwell Journals, 2017)
Roller Compacted Concrete (RCC) is a special type of dry mixed concrete having similar ingredients and properties as conventional concrete but with lower water/cement, lower paste content, higher fine aggregate content. RCC should be made in such a way that they will be easier to compact and should have adequate properties for the roller compaction. The best strength in RCC is obtained when the optimum compaction is achieved and this condition can only be attained at the wettest mix that can be able to support vibratory roller without sinking. Water reducing admixtures has been used in RCC to increase its consistency by helping in the distribution of the little paste content, lower its water/cement ratio and improve its strength. In this study, the effect of superplasticizer dosage on the properties of Roller Compacted Rubbercrete (RCR) made by partial replacement of fine aggregate with crumb rubber in Roller Compacted Concrete (RCC) pavement was studied. Superplasticizer was added at 0, 1 and 2 by weight of cementitious materials and fine aggregate was replaced with crumb rubber at 0, 10, 20 and 30. The results showed that crumb rubber decreases consistency and compressive strength of RCR and increases its flexural strength. Similarly, addition of superplasticizer further decreases consistency of RCR and increases its compressive strength. In addition, the flexural strength of RCR increases with addition of 1 superplasticizer and decreases with addition 2 superplasticizer. The recommended dosage of superplasticizer for use in RCR is 1 by weight of cementitious materials. © Medwell Journals, 2017.